Case Report: Management of Recurrent Ovarian Squamous Cell Carcinoma With PD-1 Inhibitor - Song, Xiao-chen; Wang, Yong-xue; Yu, Mei; Cao, Dong-yan; Yang, Jia-xin (Frontiers in Oncology, 2022)
Malignant transformations, such as ovarian squamous cell carcinoma (SCC) in ovarian mature cystic teratoma (OMCT), are rare tumors. The management of recurrent disease is still a challenge, and the gene mutations involved remain unclear. We herein report a recurrent case of ovarian SCC with a PIK3CA gene variation and immunohistochemical staining of programmed death-ligand 1 (PD-L1) >10%. This patient achieved clinical remission after platinum-based effective chemotherapy and programmed death 1 (PD-1) immunotherapy.